Failure point : how to determine burning building stability - Hill, Howard, 1948- (PennWell, 2012)
In his new book, author Howard J. Hill describes building construction features and how to recognize collapse dangers for all types of buildings and construction methods. The book includes discussions about key elements that warn of imminent fire-induced collapse and how to prevent injuries to operating personnel. Also, this text covers adapting risk/benefit techniques to manage firefighting personnel on the fireground and how building codes affect fire-induced building collapses. Failure Point is an important resource for chief officers, company officers, firefighters, and code officials. It meets Fire and Emergency Services Higher Education (FESHE) requirements for the Building Construction for Fire Protection course.
Keywords: Building failures -- Risk assessment.; Emergency management.; Fire extinction -- Accidents -- Prevention.; Live loads.; Structural failures -- Risk assessment.; elektronické knihy; electronic books